Carbon-encapsulated MXene membrane for purifying methylbenzene in benzaldehyde industrial wastewater as well as preparation method and application of carbon-encapsulated MXene membrane

By using V-type MXene material to prepare carbon-encapsulated MXene composite films, the difficulty of recycling toluene in benzaldehyde industrial wastewater was solved, efficient toluene purification and separation was achieved, and the membrane had good stability and durability.

CN119896979APending Publication Date: 2025-04-29HUNAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510306241.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the benzaldehyde industrial production, there are difficulties in recycling toluene, and the prior art is difficult to efficiently separate and purify toluene, resulting in waste of resources and environmental pollution.

Method used

Using V-based MXene material as the precursor, carbon-encapsulated MXene nanosheets were prepared by polysaccharide coating and hydrothermal carbonization treatment to form a carbon-encapsulated MXene composite film, and deposited on the base film by drop coating to achieve efficient purification of toluene.

Benefits of technology

This method can significantly improve the selective permeability of toluene, reduce the transmittance of other solvents, and achieve efficient toluene purification and separation. The membrane has good stability and durability, which is suitable for complex industrial environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896979A_ABST
    Figure CN119896979A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-encapsulated MXene membrane for purifying methylbenzene in benzaldehyde industrial wastewater as well as a preparation method and application of the carbon-encapsulated MXene membrane, and relates to the technical field of membrane separation and purification. The preparation method comprises the following steps: selecting a V-series MXene material as a precursor; carrying out coating treatment on the MXene material by utilizing polysaccharide; carrying out hydrothermal carbonization treatment on the coated MXene material, so as to obtain a carbon packaged MXene nanosheet; the preparation method comprises the following steps: dispersing a carbon-encapsulated MXene nanosheet in a solvent to form a dispersion liquid; and depositing the dispersion liquid on the surface of the base film by adopting a dispensing method to prepare the carbon-encapsulated MXene composite film. According to the invention, the carbon-encapsulated MXene film with excellent selective permeability can be prepared. The membrane can efficiently permeate toluene molecules, and shows lower transmittance to other solvents, so that efficient toluene purification and separation are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane separation and purification, and in particular to a carbon-encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater, and a preparation method and application thereof. Background Art

[0002] In the industrial production of benzaldehyde, toluene is a key raw material, and its recycling is of great significance. Toluene recovery can significantly reduce the production cost of enterprises and reduce the risk of environmental pollution. Membrane separation technology separates toluene from other solvents or impurities through a selectively permeable membrane, which can achieve efficient recovery and reduce environmental pollution. Compared with traditional recovery methods, membrane separation has the advantages of low energy consumption, simple operation, and less impact on the environment. Therefore, it has received widespread attention and application in toluene recovery.

[0003] V-series MXene materials (such as V2CT x 、V4C3T x 、V3C2T x V-series MXene materials are two-dimensional materials composed of transition metals (such as vanadium) and elements such as carbon or nitrogen, and are an important branch of the MXene family. MXene materials are two-dimensional compounds with excellent physical and chemical properties and are suitable for the field of membrane separation. V-series MXene materials have significant advantages due to their unique two-dimensional layered structure and excellent physical and chemical properties, especially in applications such as gas separation, liquid separation and wastewater treatment. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a carbon-encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater, which can prepare a carbon-encapsulated MXene membrane with excellent selective permeability. The membrane can efficiently permeate toluene molecules while showing a lower permeability to other solvents, thereby achieving efficient toluene purification and separation.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a carbon-encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater comprises the following steps: A V-series MXene material is selected as a precursor; the MXene material is coated with polysaccharide; the coated MXene material is subjected to hydrothermal carbonization to obtain carbon-encapsulated MXene nanosheets; the carbon-encapsulated MXene nanosheets are dispersed in a solvent (such as ethanol) to form a dispersion; the dispersion is deposited on the surface of the base film by a drop coating method to prepare a carbon-encapsulated MXene composite film.

[0006] Furthermore, the V-based MXene material is selected from V2CTx 、V4C3T x 、V3C2T x One of them.

[0007] Furthermore, the polysaccharide is selected from one of xylan, mannan and starch.

[0008] Furthermore, the base membrane is an alumina base membrane (such as a commercial alumina ceramic membrane).

[0009] Furthermore, the mass ratio of the V-series MXene material to the polysaccharide is 1:0.2 to 1:0.5, that is, 1:(0.2-0.5), for example, 1:0.2 or 1:0.4 or 1:0.5.

[0010] Furthermore, the temperature of the hydrothermal carbonization treatment is 120 to 200 degrees (for example, 120 degrees or 150 degrees or 200 degrees), and the reaction time is 12 to 24 hours (for example, 12 hours or 24 hours).

[0011] Furthermore, the concentration of the carbon-encapsulated MXene nanosheets in the dispersion is 0.01 to 0.05 g / L, for example, 0.01 g / L or 0.02 g / L or 0.05 g / L.

[0012] Furthermore, when the dispersion is deposited on the surface of the base film by the drop coating method, the drop coating time is within 1 minute.

[0013] Another object of the present invention is to provide a carbon-encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater, which is prepared by the above-mentioned preparation method. The carbon-encapsulated MXene membrane can effectively and selectively permeate toluene molecules, while having a lower permeability to other solvents.

[0014] In addition, the carbon-encapsulated MXene membrane described above can be used as a pervaporation membrane for the recovery of toluene solvent in benzaldehyde industrial wastewater.

[0015] The carbon-encapsulated MXene membrane prepared by the present invention combines the high specific surface area of ​​MXene and the good chemical stability of carbon materials, so that it can efficiently and selectively separate toluene from other solvents or impurities, providing excellent purification effects. The carbon encapsulation layer can effectively protect the MXene material from oxidation, improve the long-term stability of the membrane in high temperature and strong acid and alkali environments, and extend the service life of the membrane. The layered structure of MXene and the adjustability of carbon encapsulation allow the pore size of the membrane to be precisely controlled, optimize the permeation path of toluene molecules, and further improve the separation performance. The carbon-encapsulated MXene membrane is particularly suitable for efficient recovery of toluene from benzaldehyde industrial wastewater due to its excellent separation performance and stability. It can also maintain long-term stable operation in complex industrial environments, showing excellent durability and adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The carbon-encapsulated MXene (V3C2T x ) SEM images of nanosheets; Figure 2 Graph showing the flux and separation factor of the composite membranes prepared in Examples 1-5. DETAILED DESCRIPTION

[0017] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.

[0018] Toluene purification and separation test: In this experiment, 5 wt% toluene / ethanol solution was used as the feed liquid, and the toluene permeation performance of the carbon-encapsulated MXene membrane was evaluated using a pervaporation device. The prepared carbon-encapsulated MXene membrane was placed in a membrane pool, and then the membrane assembly was placed in a 60°C oven. A 5 wt% toluene / ethanol solution was used as the feed liquid, the liquid flow rate was 0.4 L / min, and the permeation side was connected to a vacuum pump for decompression. The permeation side components were recovered by cold trap condensation. The temperature of the vapor side of the membrane module was set (80°C), and the condensation side was kept at a lower temperature (20°C). During the experiment, the permeated toluene samples and condensate samples were collected regularly, and the liquid samples were collected from the condensation side, and the collected volume and flow rate were recorded. The concentration of toluene at different time points was determined using analytical methods such as gas chromatography (GC) and mass spectrometry (MS). The pervaporation performance of the membrane is evaluated by two parameters: permeation flux (J) and separation factor (α), which are calculated using the following formula:

[0019] where m is the total mass collected on the permeate side after t hours, and A is the effective membrane area (7 cm 2 ), X and Y are the mass fractions of toluene in the feed solution and the permeate, respectively. Example 1

[0020] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: V2CT purchased from Beike Nanotechnology Co., Ltd. xMXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.1g of xylan was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.05g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50 o C drying oven for 12 hours and then taken out for the next step.

[0021] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 5060 g·m -2 ·h -1 , the separation factor is 37.5. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity. Example 2

[0022] Carbon Encapsulation V4C3T x Preparation process of MXene composite membrane: V4C3T purchased from Beike Nanotechnology Co., Ltd. x MXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.1g of xylan was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.05g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50o C drying oven for 12 hours and then taken out for the next step.

[0023] Carbon Encapsulation V4C3T x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 4208 g·m -2 ·h -1 , the separation factor is 42.7. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity. Example 3

[0024] Carbon Encapsulation V3C2T x Preparation process of MXene composite membrane: V3C2T purchased from Beike Nanotechnology Co., Ltd. x MXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.1g of xylan was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.05g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50 o C drying oven for 12 hours and then taken out for the next step.

[0025] Carbon Encapsulation V3C2T x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 5212 g·m -2 ·h -1, the separation factor is 41.9. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity.

[0026] Example 3 Carbon encapsulated MXene (V3C2T x ) The electron microscope image of the nanosheet can be found in Figure 1 . Example 4

[0027] Carbon Encapsulation V3C2T x Preparation process of MXene composite membrane: V3C2T purchased from Beike Nanotechnology Co., Ltd. x MXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.25g of xylan was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.05g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50 o C drying oven for 12 hours and then taken out for the next step.

[0028] Carbon Encapsulation V3C2T x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 3950 g·m -2 ·h -1 , the separation factor is 45.8. The prepared composite membrane can run continuously for 7 days with stable flux and selectivity. By adjusting the polysaccharide content and increasing the thickness of the carbon layer, the toluene selectivity is improved. Example 5

[0029] Carbon Encapsulation V3C2T x Preparation process of MXene composite membrane: V3C2T purchased from Beike Nanotechnology Co., Ltd. xMXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.1g of xylan was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.01g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.01g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50 o C drying oven for 12 hours and then taken out for the next step.

[0030] Carbon Encapsulation V3C2T x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80°C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 8766 g·m -2 ·h -1 , the separation factor is 21.2. Reducing the concentration of carbon encapsulated MXene dispersion leads to a decrease in separation layer thickness and an increase in flux, but a serious decrease in selectivity. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity.

[0031] The flux and separation factor of the composite membrane prepared in Examples 1-5 can be found in Figure 2 . Example 6

[0032] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: V2CT purchased from Beike Nanotechnology Co., Ltd. xMXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.1g of mannan was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.05g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50 o C drying oven for 12 hours and then taken out for the next step.

[0033] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 4989 g·m -2 ·h -1 The separation factor was 37.6. The prepared composite membrane could run continuously for 7 days with stable flux and selectivity. The flux of the membrane prepared by using mannan was slightly lower than that of xylan, but the selectivity was similar. Example 7

[0034] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: V2CT purchased from Beike Nanotechnology Co., Ltd. xMXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. Subsequently, 0.1g of starch was added to the dispersion and ultrasonicated for 30min to obtain a mixed solution. The mixed solution was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L carbon-encapsulated MXene dispersion. Take 1mL of the prepared 0.05g / L carbon-encapsulated MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in 50 o C drying oven for 12 hours and then taken out for the next step.

[0035] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed liquid volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 5096 g·m -2 ·h -1 , the separation factor is 36.6. The prepared composite membrane can run continuously for 7 days, and the flux and selectivity remain stable. The flux of the membrane prepared by using starch is slightly higher than that of xylan, but the selectivity is lower. Example 8

[0036] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The other conditions of this embodiment are the same as those of embodiment 1, except that the hydrothermal carbonization temperature is changed to 200 degrees.

[0037] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed liquid volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 4026 g·m -2 ·h -1The separation factor was 39.9. The prepared composite membrane could run continuously for 7 days with stable flux and selectivity. The flux of the membrane prepared by using MXene treated at a higher temperature decreased and the selectivity increased. Example 9

[0038] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The other conditions of this example are the same as those of Example 1, except that the hydrothermal carbonization time is changed to 24 h.

[0039] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 5022 g·m -2 ·h -1 The separation factor is 37.3. The prepared composite membrane can run continuously for 7 days with stable flux and selectivity. The values ​​of the membrane prepared by using MXene treated for a longer time do not change much. Example 10

[0040] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The other conditions in this example were the same as those in Example 1, except that the weight of xylan was changed to 0.25 g.

[0041] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80°C, 100Pa vacuum, 1L feed liquid volume, 0.4L / min feed rate, and 1h operation time. The total permeate flux of the membrane prepared under these conditions was 4677g·m -2 ·h -1 , the separation factor is 38.2. The prepared composite membrane can run continuously for 7 days, and the flux and selectivity remain stable. The carbon encapsulation of MXene formed by using more xylan is thicker, and the flux of the prepared membrane decreases. Embodiment 11

[0042] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The preparation conditions of this example are consistent with those of Example 1.

[0043] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test, and the concentration of the toluene / ethanol solution was adjusted; The toluene / ethanol solution with a concentration of 1wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were 80℃, 100Pa of vacuum, 1L of feed liquid volume, 0.4L / min of feed rate, and 1h of operation time. The total permeation flux of the membrane prepared under these conditions was 3912g·m -2 ·h -1 , the separation factor is 42.2. The prepared composite membrane can run continuously for 7 days, and the flux and selectivity remain stable. The reduction of toluene content will lead to an increase in the separation factor, but a decrease in the total flux. Example 12

[0044] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The preparation conditions of this example are consistent with those of Example 1.

[0045] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test, and the concentration of the toluene / ethanol solution was adjusted; A 3wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80°C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 4318 g·m -2 ·h -1 , the separation factor is 40.2. The prepared composite membrane can run continuously for 7 days, and the flux and selectivity remain stable. The reduction of toluene content will lead to an increase in the separation factor, but a decrease in the total flux. Example 13

[0046] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The other conditions in this example were the same as those in Example 1, except that the weight of xylan was changed to 0.20 g.

[0047] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed liquid volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 4818 g·m -2 ·h -1 , the separation factor is 37.9. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity. Embodiment 14

[0048] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The other conditions of this embodiment are the same as those of embodiment 1, except that the hydrothermal carbonization temperature is changed to 150 degrees.

[0049] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 4506 g·m -2 ·h -1 , the separation factor is 38.9. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity. Embodiment 15

[0050] Carbon Encapsulated V2CT x Preparation process of MXene composite membrane: The other conditions of this example are consistent with those of Example 1, except that the concentration of the carbon-encapsulated MXene dispersion is changed to 0.02 g / L.

[0051] Carbon Encapsulated V2CT x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed liquid volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 7117 g·m -2 ·h -1 , the separation factor is 28.5. The prepared composite membrane can operate continuously for 7 days with stable flux and selectivity. Comparative Example

[0052] Carbon Encapsulation V3C2T x Preparation process of MXene composite membrane: V3C2T purchased from Beike Nanotechnology Co., Ltd. x MXene material (0.5g) was added to 40ml deionized water and ultrasonicated for 30min to obtain a uniformly dispersed MXene dispersion. The dispersion was transferred to a 50mL polytetrafluoroethylene reactor for hydrothermal carbonization at a temperature of 120 degrees and a reaction time of 12h. After the reaction, it was centrifuged with ethanol and dried for later use. The prepared carbon-encapsulated MXene was dispersed in ethanol to obtain a 0.05g / L MXene dispersion. Take 1mL of the prepared 0.05g / L MXene dispersion and deposit it on the surface of the alumina-based film by drop coating within 1min. The solvent was evaporated at room temperature to obtain a uniform film surface, and then the carbon-encapsulated MXene composite film was placed in a 50 o C drying oven for 12 hours and then taken out for the next step.

[0053] Carbon Encapsulation V3C2T x Performance test of MXene composite membrane: The experiment was conducted with reference to the conditions in the toluene purification and separation test; A 5 wt% toluene / ethanol solution was used as the permeate feed liquid. The pervaporation operating conditions were 80 °C, 100 Pa vacuum, 1 L feed volume, 0.4 L / min feed rate, and 1 h operation time. The total permeate flux of the membrane prepared under these conditions was 3207 g·m -2 ·h -1 , the separation factor is 15.9. The prepared composite membrane can only run for 10 h, and the flux and selectivity then drop sharply. This is because MXene is not coated by the carbon layer, and MXene is easily oxidized to metal oxides, which in turn causes the separation layer to be destroyed.

[0054] In general, the present invention utilizes different types of V-series MXene materials, treats them with polysaccharides, and then hydrothermally carbonizes them to obtain carbon-encapsulated MXene nanosheets. The carbon-encapsulated MXene nanosheets are then dispersed in a solvent to form a dispersion, and the dispersion is deposited on a base film by a drop coating method to prepare a carbon-encapsulated MXene composite membrane. The prepared flat membrane has excellent toluene separation performance, can effectively and selectively permeate toluene molecules, and has a low permeability to other solvents. The experimental results show that the membrane can maintain a high separation efficiency in toluene solutions of different concentrations, and has good stability and durability, and is suitable for application in the fields of benzaldehyde industrial wastewater treatment and organic solvent recovery.

[0055] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

[0056] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.

Claims

1. A method for preparing a carbon-encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater, characterized in that: The following steps are involved: Select V-series MXene materials as precursors; Using polysaccharides to coat MXene materials; The coated MXene material is subjected to a hydrothermal carbonization treatment to obtain carbon-encapsulated MXene nanosheets; the carbon-encapsulated MXene nanosheets are dispersed in a solvent to form a dispersion; The dispersion was deposited on the surface of the base film by drop coating to prepare the carbon-encapsulated MXene composite film.

2. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: The V-series MXene material is selected from V2CT x 、V4C3T x 、V3C2T x One of them.

3. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: The polysaccharide is selected from one of xylan, mannan and starch.

4. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: The base film is an aluminum oxide base film.

5. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: The mass ratio of the V-series MXene material to the polysaccharide is 1:(0.2-0.5).

6. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: The temperature of the hydrothermal carbonization treatment is 120 to 200 degrees, and the reaction time is 12 to 24 hours.

7. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: The concentration of the carbon-encapsulated MXene nanosheets in the dispersion is 0.01 to 0.05 g / L.

8. The method for preparing a carbon-encapsulated MXene film for purifying toluene in benzaldehyde industrial wastewater according to claim 1, characterized in that: When the dispersion is deposited on the surface of the base film by the drop coating method, the drop coating time is within 1 minute.

9. A carbon-encapsulated MXene membrane for purifying toluene from benzaldehyde industrial wastewater, characterized in that: The method for preparing a carbon-encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater according to any one of claims 1 to 8 is used.

10. The use of the carbon encapsulated MXene membrane for purifying toluene in benzaldehyde industrial wastewater according to claim 9, characterized in that: Carbon-encapsulated MXene membrane was used as a pervaporation membrane to recover toluene solvent from benzaldehyde industrial wastewater.